An illustrated history of Indian literature in English - Mehrotra, Arvind Krishna (Delhi : Permanent Black in association with Ravi Dayal Publishers, New Delhi, 2003)
Contributed articles.
Includes bibliographical references and index.
Keywords: Indic literature (English) -- 19th century -- History and criticism; Indic literature (English) -- 20th century -- History and criticism